A study on aroma release and perception of saffron ice cream using in-vitro and in-vivo approaches. (October 2020) - Feyzi, Samira; Varidi, Mehdi; Housaindokht, Mohammad Reza; Es'haghi, Zarrin; Romano, Raffaele; Piombino, Paola; Genovese, Alessandro
Abstract: The effect of fat nature (dairy fat, and combination of dairy fat with sunflower oil) and its substitution with whey protein isolate (WPI) (0, 5% and 7.5%) on aroma release and perception from six saffron ice creams was studied through in-vitro, retro- and ortho-nasal approaches, and sensory evaluation. Compared with full-fat (10% fat) saffron ice creams, light (5% fat) and low-fat (2.5% fat) samples were accompanied with more safranal release into the vial headspace (0.0126, 0.0177, and 0.0220 ppm, respectively) and mouth cavity (100%, 153.6%, and 235.6%, respectively). Gas chromatography/Olfactometry showed that the most sensation of the majority of aroma compounds was from - low-fat and dairy fat-based samples. Results of in-mouth and ortho-nasal pathways studies coincided, indicating no significant difference ( P <0.05) in aroma release among full-fat and light samples with two different fat types. These findings would suggest WPI as an appropriate fat replacer in light saffron ice creams for aroma delivery purposes. Graphical abstract: Unlabelled Image Highlights: Saffron ice cream was produced altering fat type and content. WPI was appropriate aroma carrier and fat replacer in light ice creams. Dairy fat-based ice creams were accompanied with higher modified frequency (MF%). Safranal and keto-isophorone had the highest MF% in saffron powder and ice creams. There was no difference in ortho-nasal perception of full-fat and light samples.